Prevalencia de micoplasmosis felina en la ciudad de Machala en el 2012 - Martínez Cruz, Alfredo Fabián (2012)
The work of investigation was carried out in Machala's city to level of urban parishes, there were selected to 152 cats at random which a sample of blood was extracted and they there was realized a blood smear, which was fixed by methanol and then dyed by colouring Giemsa. Later these smears were moved to the laboratory of parasitology of the Faculty of Agricultural Sciences of Machala's Technical University to be observed to the microscope by an aim 100 X (dip) determining the presence of Mycoplasma. Of 152 sampled cats 12 were positive representing 7,89 % of the total sampled population. For the variable age, of 76 cats of more than one year studied 5 turned out to be positive to the disease representing 6,57 % and of 76 cats of less than one year of age studied 7 turned out to be positive to the disease, representing 9,21 % of the studied population As for the variable race of 76 pure animals 5 turned out to be positive, this represents 6,57 % of the total population. Of equal way I sample 76 half-caste cats turning out to be positive 7, which represents 9,21 % of the total sampled population. For variable sex, there was obtained that of 82 sampled females, 7 turned out to be positive representing 8,53 %. Of 70 sampled males 5 turned out to be positive, which 7,14 % represents.